Highly oriented macroporous graphene hybrid monoliths for lithium ion battery electrodes with ultrahigh capacity and rate capability - Huang, Yanshan; Wu, Dongqing; Jiang, Jianzhong; Mai, Yiyong; Zhang, Fan; Pan, Hao; Feng, Xinliang (Nano Energy, 2015)
The highly oriented macroporous graphene monoliths hybridized with carbon-coated metal oxide or phosphate (C/M/GM) with core/shell structure were fabricated by an ice-templating co-assembly of M/GO nanosheets (metal oxide/phosphates decorated graphene oxide) and polyvinyl alcohol (PVA), and following thermal treatment. With either tin oxide (SnO2) or iron phosphate (FePO4), the resulting C/M/GMs possess periodic macropores with diameters ranging from 5 to 20μm and high loading contents of active components ( 70wt%). Served as the anode in LIBs, C/SnO2/GM maintains an ultrahigh capacity of 1665mAhg-1 at a current density of 0.2Ag-1 for 200 cycles. Even at an ultrafast charge rate of 10Ag-1, a decent capacity of 300mAhg-1 can still be achieved, with excellent cycling stability. And C/FePO4/GM also delivers a highly reversible capacity of 175mAhg-1 at a current density of 0.05Ag-1 for 150 cycles and a good capacity of 57mAhg-1 at 2Ag-1 when as the LIB cathode electrode.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Core/shell; Graphene; Hybrid; Lithium-ion battery; Macrospore